2018
DOI: 10.1038/s41598-018-29465-9
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor (PEDF) as a Regulator of Wound Angiogenesis

Abstract: Although the inflammatory and proliferative phases of wound healing have been well described, much less is known about how healing resolves. During the resolution phase, pruning of the capillary bed and maturation of capillaries occurs and influences the final strength and fidelity of the wound. PEDF, an endogenous anti-angiogenic factor, is produced in wounds and may contribute to the removal of capillaries during wound resolution. This study utilized PEDF−/− mice to examine how PEDF influences wound angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Most striking was the difference in capillary content at day 10 post-wounding, with WT wounds showing nearly 4 times as much capillary content as diabetic wounds at this time point (p< 0.01) ( Fig 1A and 1B). This time point was of particular significance because previous studies in our lab showed that days 7-10 represent the peak of angiogenesis in normally healing wounds [9,10,21]. These results demonstrated a deficit in diabetic wound healing during the crucial switch from capillary growth to pruning and maturation.…”
Section: -D and 3-d Vascular Architecture Is Significantly Altered Imentioning
confidence: 74%
See 3 more Smart Citations
“…Most striking was the difference in capillary content at day 10 post-wounding, with WT wounds showing nearly 4 times as much capillary content as diabetic wounds at this time point (p< 0.01) ( Fig 1A and 1B). This time point was of particular significance because previous studies in our lab showed that days 7-10 represent the peak of angiogenesis in normally healing wounds [9,10,21]. These results demonstrated a deficit in diabetic wound healing during the crucial switch from capillary growth to pruning and maturation.…”
Section: -D and 3-d Vascular Architecture Is Significantly Altered Imentioning
confidence: 74%
“…Significantly lower levels of CXCR3 and its ligand, CXCL10, both of which are well known to be important to wound resolution [36], were observed in diabetic wounds. The expression of SPRY2 [37], TSP1 [38], and PEDF [9,10], all factors that are known to promote vascular pruning in wounds, was also significantly decreased in wounds from db/db mice. Interestingly TSP1 may play a dual role in wounds, as it can affect not only local capillary regression, but also has been described to have a positive effect on the activity of vascular precursor cells.…”
Section: Functional Categorymentioning
confidence: 96%
See 2 more Smart Citations
“…The length of the newly formed epidermis was calculated by adding the lengths of the neoepithelial tongues on both sides of the wound from the tip of the epidermis to the site of the first hair follicle at the wound margin. The surface of CD31 þ blood vessels (with open and closed lumen) was measured in 5 different fields on CD31-labeled sections, and the data are presented as a percentage of the total surface of the wound (Cho et al, 2006;Khosrotehrani et al, 2011;Michalczyk et al, 2018). Double stained Ki67/CD31 cells were used as an index of neovascularization in wounds.…”
Section: Immunohistochemistry and Immunofluorescence Stainingmentioning
confidence: 99%